Collaborative Decision-Making in Non-formal Planning Settings - Nogueira, Fernando (2018)
Planning initiatives outside the formal planning system can constitute a favourable environment for implementing and analysing collaborative decision-making processes. The conceptualisation of the decision-making context in the light of the Policy Network analysis helps to better understand the underlining conditions, as well as their influence in the outcomes. In the case under analysis, were the decision-making conditions were of co-responsibility and power-sharing, the challenge has been to warrant the effectiveness of the decisions, which lies, as is argued, in the reliability of the framework for decision-making and in the ability to translate the collaborative participation outputs into actions at different time-frames. Moreover, as the case-study deals with strategic spatial planning, a future oriented approach is needed to warrant the flexibility and robustness of the plan in addressing the uncertainty associated with long term objectives. Those are the critical issues to be handled in the multi-criteria analysis (MCA) framework which sustains the analytical hierarchy process (AHP) that was used to support the decision-making process.